Analysis Of Islamic Educational Facilities And Infrastructure: Analisis Perencanaan Sarana Dan Prasarana Pendidikan Islam - Hasanah, Amalia; Candraini, Hesti; Mujahidin, Endin (Civilization Research: Journal of Islamic Studies, 2025)
In order to improve the quality of learning and student achievement in the classroom and at school, educational planning is an important aspect that must be considered. This includes infrastructure and facilities. This study aims to analyze the planning of Islamic education facilities and infrastructure. The method used in this research is qualitative with a qualitative descriptive analysis approach. Based on the results of the research, facilities and infrastructure are one of the factors that can improve the quality of educational institutions and students in addition to curriculum, methods, educators and education personnel. Facilities and infrastructure should be tailored to the needs and in line with the vision and mission of the educational institution itself. To achieve educational goals, adequate educational facilities and infrastructure are needed, including planning, goals and benefits, planning principles, procedures, classification, procurement of educational facilities and infrastructure. Procurement of planned facilities and infrastructure will produce good and appropriate facilities and infrastructure, so that the teaching and learning process will be successful with the support of adequate facilities and infrastructure.